Comparison of children diagnosed with cerebral palsy in a private cord blood bank to an epidemiological sample. (September 2018) - Mazonson, Peter; Kane, Mark; Colberg, Kelin; Harris, Heather; Brown, Heather; Mohr, Andrew; Santas, Chris; Sandler, Adrian
Highlights: LUSTRE studies children with CP from a large private US cord blood bank. LUSTRE subjects with CP were compared to a US population-based CP cohort. The two groups differed demographically but mobility, functional status, and comorbidities were similar. LUSTRE may be a valuable data source for the characterization of individuals with CP, including those seeking CB infusions. Abstract: Background: Although cord blood (CB) stem cell research is being conducted for treatment of cerebral palsy (CP), little is known about children with CP and stored CB. Aims: To compare demographic and clinical characteristics of children with CP and stored CB to children with CP identified in a population-based study. Methods and Procedures: The Longitudinal Umbilical Stem cell monitoring and Treatment REsearch (LUSTRE®) Registry recruited children from the largest US private CB bank. Demographics, co-morbidities, and gross motor function (GMFCS level and walking ability) were collected and, where possible, compared with the CDC's Autism and Developmental Disabilities Monitoring (ADDM) Network. Outcomes and Results: 114 LUSTRE participants were compared to 451 ADDM participants. LUSTRE participants were more likely to be white, but sex distribution was similar. Co-morbidities (autism and epilepsy) and functional mobility were also similar. Conclusions and Implications: The results of this analysis suggest that while children diagnosed with CP and with access to stored CB differ from a broader population sample in terms of demographics, they have similar clinical severity and comorbidity profiles. As such, LUSTRE may serve as a valuable source of data for the characterization of individuals with CP, including individuals who have or will receive CB infusions.